Accesslaw annotations on Philippine statutes, v. 2 public law (the laws on the state structure, powers, relations and regulations). (Laws annotated)
Volume 2 of the Laws Annotated series, this is a full-text database of Philippine laws of permanent and general application, organized by section. Links can be accessed to check on the present status of the law as well as its statutory history.